Patient-Specific Design of Prosthesis for Below Knee Amputee: Analysis Between Different Gait - Baharuddin, Muhammad Hanif; Ab Rashid, Amir Mustakim; Abdullah, Nik Nur Ain Azrin; Ramlee, Muhammad Hanif (International Journal of Integrated Engineering, 2024)
Major that often associated with prosthetic leg are poor comfort and high cost. The study is conducted to construct custom-made passive below knee prosthesis and to analyse the response to applied load in different gait condition. The scope of the study is the utilization of three-dimensional printing material, acrylonitrile butadiene styrene (ABS) in the manufacturing of prosthetic leg socket and pylon whereas the foot made from polyurethane. By using the Sense three-dimensional scanner, the subject’s residual leg was scanned. SolidWorks and Meshmixer were the software used for the three-dimensional designing of prosthetic leg parts. By using 3-Matic, aligning and meshing were carried out. von Mises stress and displacement of model applied with axial load were obtained from simulation using Marc Mentat. The load applied for midstance, heel strike and toe off phases were 350 N, 1545 N and 2450 N, respectively. The constraints position was different for each phase. The peak stress of the model was reported during toe off (20.86 MPa) followed by heel strike (13.41 MPa) and midstance (4.89 MPa). The stress during all three phases not exceeding the yield of respective materials. In displacement, the model experience highest displacement (54.95 MPa) during toe off and the lowest during midstance (6 mm). In conclusion prosthetic leg with ABS components shows acceptable durability during different gait.